(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article examines the concept of the verb, one of the main categories of Arabic grammar. In Arabic grammar, the verb is defined as one of the three types of words, and its definition, tense, mood, and conjugation system are analyzed based on Sibawayh’s "Al-Kitab" and A. Abdujabborov’s textbook "The Arabic Language." Additionally, the comparative relationship between the verb category in Arabic and the verb class in Uzbek is studied, and the similarities and differences are identified.